The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12985-016-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly activated p53 contributes to selectively increased apoptosis of latently HIV-1 infected cells upon treatment of anticancer drugs

Abstract: BackgroundDespite the successful inhibition of human immunodeficiency virus type 1 (HIV-1) replication by combination antiretroviral therapy, cells latently infected with HIV-1 remaining in patients are a major obstacle for eradication of HIV-1 infection. The tumor suppressor factor p53 is activated by HIV-1 infection, and restricts HIV-1 replication. However, a therapeutic strategy based on p53 activity has not been considered for elimination of latently infected cells.MethodsApoptotic cells were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Thus, the data presented in this paper and the observations made by others support the notion that the innate immunity is the stress-response system strongly influenced by p53. Moreover, upregulation of antiviral genes by CPT or A + N is another observation in the growing body of evidence that anticancer chemotherapeutic agents have strong antiviral properties resulting from upregulation innate immunity genes [55]. This property of anticancer drugs must be carefully considered when planning for the anticancer strategies combining the use of oncolytic virotherapy with chemotherapeutic agents [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the data presented in this paper and the observations made by others support the notion that the innate immunity is the stress-response system strongly influenced by p53. Moreover, upregulation of antiviral genes by CPT or A + N is another observation in the growing body of evidence that anticancer chemotherapeutic agents have strong antiviral properties resulting from upregulation innate immunity genes [55]. This property of anticancer drugs must be carefully considered when planning for the anticancer strategies combining the use of oncolytic virotherapy with chemotherapeutic agents [56].…”
Section: Discussionmentioning
confidence: 99%
“…The human homolog of a member of the GLI oncogene family, GLI2 (also termed hGLI2), helps HTLV1 infection progression as the simultaneous binding of hGLI2 and CREB seems critical for TAX protein to activate transcription [240]. HIV [241], HCV [242], HBV [243,244], EBV [245], and KSHV [246] utilize MYC and cellular STAT3 for infected cell proliferation, the persistence of herpesviruses latency, and inhibition of viral reactivation. HIV [247], HCV [248], HBV [249], EBV and KSHV [250,251] infected cells secrete cytokines and chemokines to regulate viral pathogenesis, evade host immune response (Toll-like receptors; TLRs and inflammasome), angiogenesis, and selectively chemoattracts T cells, activation and migration of immune cells.…”
Section: Hh Signaling Pathways During Infections and Viral Malignanciesmentioning
confidence: 99%
“…It was found that by mediating DNA demethylation in host cells, 5-aza led to several outcomes; on the one hand, it reduced the expression of HPV genes and on the other hand, it caused p53 protein stabilization that in turn induced p53-dependent apoptosis [ 74 ]. Others have shown that treatment with anticancer chemotherapeutic agents, such as 5-fluorouracil (5-FU), can be used also against HIV-1 latently-infected T-cells, since 5-FU also stabilizes p53 leading to increased levels of p53-dependent apoptosis [ 75 ].…”
Section: Targeting Wtp53 As a Future Clinical Approach For Viral Imentioning
confidence: 99%